Penerapan scaffolding untuk pencapaian kemampuan pemecahan masalah matematis - Elis Nurhayati (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2016)
The purpose of this study was to analyse the achievement of mathematical problem-solving ability through scaffolding application. This study was a quasi-experimental research with the design of pretest-posttest control group involving two classes using purposive sampling. The population in this study was the student of class VIII in one of the public junior high school in Tasikmalaya district involving two classes as a sample. The data collection technique used was test and non-test. The test instrument according to the indicator of mathematical problem-solving ability while the non-test by questionnaire. The data analyse performance quantitative using the different test of two means. The research result showed that mathematical problem-solving ability of the student who gets scaffolding learning is higher than the student who gets direct learning.